NUMERICAL SIMULATION OF WAVE DAMPENING BY A STRUCTURE OF THE HYDRO-ENGINEERING FACILITY IN COMPLETE VERTICAL PROFILE (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The article decribes the issues of numerical experimental research related to the determination of the magnitude of the waves damping when they overflow through the upper structure of a protective hydraulic structure (PHS) of an incomplete vertical profile. The presented studies were carried out in order to verify the results of physical experimental studies. Physical experimental studies were carried out in the hydrowave laboratory of the Hydrotechnical Construction Department of the Odessa State Academy of Civil Engineering and Architecture. The numerical model of the design of the PHS of an incomplete vertical profile was made similar to the conditions of the full-scale section of the coast of the Odessa Bay. The design of the PHS of an incomplete vertical profile is supposed to be located at a distance L = 200 (m) from the coastline of the protected area. At the location of the designed protective structure, the estimated water depth d = 4.0 (m). Having built the rays of refraction and transformation of waves when the waves approach the designed structure, the calculated wave height will be h = 2.4 (m); average wavelength     λ = 24.5 (m); the elevation of the upper structure of the PHS with an incomplete vertical profile relative to the calm water level was taken equal to Δ Н = +1.0 (m), the width of the superstructure of the protective structure В = 4.0 (m). As a result of numerical experiments, the height of the damped wave when it overflows through the upper structure of the PHS structure with an incomplete vertical profile onto the protected water area was htr = 0.6 (m). The results of numerical simulation differ by – 3.3% from the wave height obtained during the physical experiment.The use of PHS structures of an incomplete vertical profile, in order to protect the water areas of seaports, as well as elements of the coastal infrastructure of sea cities, will increase the investment attractiveness of creating new projects of protective and coastal protection structures, due to a decrease in the elevation of the surface part.
Keywords: numerical modeling; barrier hydraulic structure of incomplete vertical profile; wave damping.